Adequacy and enforceability of the Kenyan environmental law with regard to polythene pollution in Kenya. - Ngugi, Ian Njathi (Strathmore University, 2016)
Kenya has for a long time been affected with issues of polythene pollution which has gotten out of hand over the years with the filling up of gazetted dumpsites in Nairobi. This has brought about serious health risks through the continued dumping of hazardous material such as polythene in un-gazetted areas.The purpose of this study was to investigate the adequacy of the Kenyan legal framework on the environment and more particularly, polythene pollution in Kenya. The study also sought to show the enforceability of the already existing legal framework on how the various laws are helping to curb polythene pollution in Kenya.The study is intended to show the connection between the adequacy of the legal framework and enforceability of the law in reducing and ultimately ending polythene pollution. The study examines various jurisdictions that have dealt with the issue as a basis of determining the adequacy of Kenya 's legal framework.
Full Text